Electrochemical relative dating of Roman leaded-bronze coins from plough-soil. (December 2021) - Di Turo, Francesca; Artesani, Alessia; Pasquale, Lea; Debellis, Doriana; Traviglia, Arianna
Highlights: Showcases for the first time an adapted electrochemical dating method on Roman leaded bronze coins. Succeeds in providing relative dating of corroded and disfigured bronze coins. Pillar research on archaeological samples buried in plough-soil. Abstract: Dating of unreadable coins from non-stratigraphic archaeological contexts is a challenging task due to the lack of standard analysis pipelines. This work aimed at determining the relative chronology of a group of corroded and severely disfigured Roman leaded-bronze coins using an electrochemical dating method. The coins, found outside their original archaeological context, on the surface of the plough-soil –i.e. soil that has been thrown up by ploughing– have likely been buried across centuries in highly dynamic conditions that have effected alterations on their surface. A number of well-preserved coins part of the group, dated on basis of the letter or symbol controls, was used as a training set for the chronological reconstruction of another set of illegible coins. The corrosive compounds' layered structure formed on the coins' surface region during their circulation and burial (called patina ) was studied to retrieve information on the conservation status and deposition conditions of the coins. The characterisation of the patina highlighted the absence of highly corrosive compounds and the inverse growing tendency for copper oxide products. The lead oxide and cuprite signal ratio was used as an indicator to provide a relative dating for the illegible coins due to the deposition biography of the samples.